Associations between sleep and circadian disruption in shift work and perpetration of interpersonal violence - Rosalie B. Flinn; Rebecca M. C. Spencer; Rebecca M. C. Spencer (Frontiers in Sleep, 2023)
Research has uncovered substantial consequences of shift work on health outcomes through disruption of sleep and circadian rhythms. Less explored is how the effects of shift work on sleep and circadian rhythms can facilitate interpersonal aggression and violence within the home (i.e., intimate partner violence, child abuse). Given challenges in direct studies on this topic, integration across related literature is critical. In this narrative review, we identify compounding variables centered around sleep and circadian rhythms that place shift workers at an increased risk of perpetrating interpersonal violence. Shift workers have impaired sleep and altered circadian rhythms. Associated alternations in executive functioning, stress, and alcohol use provide pathways to increase risk for interpersonal violence. A model of interactions facilitating the relationship between shift work and interpersonal violence is proposed to promote prevention efforts and motivate policy change.